A bis‐Pyrazolate Pincer on Reduced Cr Deoxygenates CO2: Selective Capture of the Derived Oxide by CrII. Issue 33 (16th May 2019) - Labrum, Nicholas S.; Chen, Chun‐Hsing; Caulton, Kenneth G.
Abstract: Reduction of the bis ‐(pyrazolyl)pyridine complex [LCr]2 with stoichiometric KC8 in THF produces a species that is reactive with CO2 to produce an aggregate composed of paramagnetic K2 L2 Cr2 (CO3 ) linked by KCl into a product of formula [K2 L2 Cr2 (CO3 )]4 ⋅2KCl. X‐ray diffraction reveals a pincer hydrocarbon exterior and an inorganic interior composed of K +, Cl − and carbonate oxygens. Every Cr is five coordinate and square pyramidal, with the axial N donor weakly bonded to Cr due to the Jahn–Teller effect of a high spin d 4 configuration. Reaction with 13 CO2 confirms that carbonate here is derived from CO2, that oxide is derived from CO2, and that CO is indeed released, since it is not a competent ligand to Cr II . Guiding principles for selectivity in CO2 reduction are deduced from the diverse successful molecular constructs to date. Abstract : Chromium, an underutilized transition metal, when coupled with a pincer ligand designed to assist in storage of electrons, is capable of stoichiometrically reducing CO2 to CO and the resulting oxide is then trapped by additional CO2 to give carbonate. Aggregation of the K2 L2 Cr2 (CO3 ) unit is driven by the electrophilic stabilization provided by K + and the directed nucleophile contained in the pyrazolate arms of the pincer.